Linguistic errors made by Islamic university EFL students - Aziz, Zulfadli A.; Fitriani, Siti Sarah; Amalina, Zahria (Universitas Pendidikan Indonesia, 2020)
In a writing activity students are required to transfer their knowledge to express their ideas on both what to say and how to say it. The difficulties in applying this knowledge have become obstacles for learners in constructing good writing. Consequently, these obstacles may cause the students to make errors. By adopting the notions of Error Analysis (EA) and the Surface Strategy Taxonomy as the theoretical frameworks, this study investigates the types of linguistic errors produced by the students. Along the way the sources behind the errors were also analyzed. This study employed the qualitative method design in which the case study approach was utilized. Ellis’ five-step procedure of EA was adopted to analyze the data of essays comprising of 150-300 words written by 23 EFL students of the fourth-semester at English Department at a state university. They were purposively selected as the participants of this study. It was found that omission was the most frequent errors identified in the students’ writings. Overall, 122 (63%) cases out of 195 cases were categorized under this type of errors. The number marker, verb-tense, article, preposition, subject-verb agreement, and pronoun were the categories of frequent errors made by the students, respectively. These were followed by addition (18%), misformation (15%), and misordering (5%). Significance to the source of errors, intralingual transfer turned out to be the main reason that provoked the blunder in the students’ writings. It was apparent that some of the interlinguistic contrast was the reason behind the errors. It appeared that the diverse systematical concept between the Indonesian language and English in terms of verb conjugation factor, inflectional morpheme, and auxiliary-verb abandonment were the strong contenders of the error sources. Additionally, interlingual transfer and context of learning also took part for the reason behind the errors.